2020
DOI: 10.1002/hep.30951
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 19–Mediated Up‐regulation of SYR‐Related High‐Mobility Group Box 18 Promotes Hepatocellular Carcinoma Metastasis by Transactivating Fibroblast Growth Factor Receptor 4 and Fms‐Related Tyrosine Kinase 4

Abstract: BaCKgRoUND aND aIMS:The poor prognosis of patients with hepatocellular carcinoma (HCC) is mainly attributed to its high rate of metastasis and recurrence. However, the molecular mechanisms underlying HCC metastasis need to be elucidated. The SRY-related high-mobility group box (SOX) family proteins, which are a group of highly conserved transcription factors, play important roles in cancer initiation and progression. Here, we report on a role of SOX18, a member of the SOX family, in promoting HCC invasion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…Cho et al (2016) revealed that the overexpression of FGR was significantly associated with a shorter time to tumor recurrence in HCC by means of integrative analysis. Chen et al (2020) found an association between fibroblast growth factor receptor 4 (FGFR4) and the invasion and metastasis of HCC. Guo et al (2016) demonstrated that elevated intracellular adhesion molecule 1 (ICAM-1) expression in HCC tissues was correlated with portal vein tumor thrombus development and poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al (2016) revealed that the overexpression of FGR was significantly associated with a shorter time to tumor recurrence in HCC by means of integrative analysis. Chen et al (2020) found an association between fibroblast growth factor receptor 4 (FGFR4) and the invasion and metastasis of HCC. Guo et al (2016) demonstrated that elevated intracellular adhesion molecule 1 (ICAM-1) expression in HCC tissues was correlated with portal vein tumor thrombus development and poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal expression of oncogenes was usually derived from changes in their transcriptional activity. For instance, transcription factor SOX18 upregulates transcriptionally the expression of FGFR4 and FLT4 and promotes the metastasis of hepatocellular carcinoma [47]. We aimed to find important transcription factors that could bind to the promoter of SETDB1 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the other three FGFR family members, the function of the FGFR4 signaling pathway in cancer is less well-characterized. Recently, it has been reported that the activation of FGF19-FGFR4 signaling is closely associated with cancer development and progression Chen et al, 2019), suggesting that FGF19-FGFR4 might be an attractive target for effective anticancer therapeutics (Schadt et al, 2018;Gao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%